2021
DOI: 10.1002/alr.22923
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported olfactory and gustatory dysfunction and psychophysical testing in screening for COVID‐19: A systematic review and meta‐analysis

Abstract: Background A substantial proportion of coronavirus disease‐2019 (COVID‐19) patients demonstrate olfactory and gustatory dysfunction (OGD). Self‐reporting for OGD is widely used as a predictor of COVID‐19. Although psychophysical assessment is currently under investigation in this role, the sensitivity of these screening tests for COVID‐19 remains unclear. In this systematic review we assess the sensitivity of self‐reporting and psychophysical tests for OGD. Methods A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
(569 reference statements)
0
5
0
Order By: Relevance
“…The observed 25% prevalence of self-reported persistent chemosensory dysfunction two years post-infection seems to be high. Nevertheless, one must keep in mind that self-reports of chemosensory dysfunction poorly correlate with psychophysical test results and mostly underestimate the prevalence of chemosensory dysfunction [ 22 , 23 , 42 ]. Therefore, the usage of psychophysical tests is recommended to assure a more reliable assessment of chemosensory function [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed 25% prevalence of self-reported persistent chemosensory dysfunction two years post-infection seems to be high. Nevertheless, one must keep in mind that self-reports of chemosensory dysfunction poorly correlate with psychophysical test results and mostly underestimate the prevalence of chemosensory dysfunction [ 22 , 23 , 42 ]. Therefore, the usage of psychophysical tests is recommended to assure a more reliable assessment of chemosensory function [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies report on PCD two years after infection, showing varied results with a self-reported prevalence of 11–61% [ 13 , 19 , 20 , 21 ]. Since self-reports tend to poorly correlate and often underestimate psychophysically measured chemosensory dysfunction, it is important to additionally apply psychophysical testing [ 22 , 23 ]. So far, only one other study reports on psychophysically tested chemosensory function after two years [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, even before COVID-19, progress was being made. Novel diagnostic methods like psychophysical olfactory testing, gustatory evoked potentials, and objective biomarkers of nerve damage are enhancing our ability to identify and characterize smell and taste deficits [ 21 ]. Meanwhile, emerging treatments ranging from corticosteroids and olfactory training to platelet-rich plasma and neuromodulation are providing new options for sensory rehabilitation [ 22 , 23 , 24 , 25 ].…”
Section: Emerging Research and Advances In Diagnosis And Treatmentmentioning
confidence: 99%
“…T he prevalence of olfactory dysfunction (OD) during and after COVID-19 has been the subject of numerous studies that reported reliable data based on psychophysical tests. [1][2][3][4][5] A common limitation of all these studies is the lack of an objective olfactory assessment prior to infection. For this reason, it has never been possible to understand exactly to what extent the SARS-CoV-2 infection impacted psychophysical scores or whether recovery was actually complete.…”
mentioning
confidence: 99%
“…The prevalence of olfactory dysfunction (OD) during and after COVID‐19 has been the subject of numerous studies that reported reliable data based on psychophysical tests 1‐5 . A common limitation of all these studies is the lack of an objective olfactory assessment prior to infection.…”
mentioning
confidence: 99%